2015
DOI: 10.1080/09291016.2015.1060679
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in stroke parameters and motor organization in front-crawl swimmers

Abstract: The aim of the present study was to examine the effects of time of day on stroke parameters and motor organization in front-crawl swimmers. In a randomized order, fourteen regional swimmers (age: 18.7 ± 1.6 years) performed maximal front crawls over 12.5m during two experimental sessions; the morning sessions were conducted between 07:00 and 09:00 h and the evening experiments were conducted between 17:00 and 19:00 h. Stroke parameters (swim velocity, stroke rate and stroke length), motor organization (arm str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, data indicate that swimming performance was better in the evening than the morning, with higher evening values for V and SR, possibly explaining the better swimming performance at this time. Circadian variations in maximum swimming performance have previously been shown in other studies (Baxter & Reilly, 1983;Ferchichi et al, 2015Ferchichi et al, , 2016Kline et al, 2007). In the present study, even though V was significantly higher in the evening compared to the morning, the mechanisms responsible for such variation are poorly understood.…”
Section: Effect Of Time-of-day Before Ramadanmentioning
confidence: 49%
See 1 more Smart Citation
“…In addition, data indicate that swimming performance was better in the evening than the morning, with higher evening values for V and SR, possibly explaining the better swimming performance at this time. Circadian variations in maximum swimming performance have previously been shown in other studies (Baxter & Reilly, 1983;Ferchichi et al, 2015Ferchichi et al, , 2016Kline et al, 2007). In the present study, even though V was significantly higher in the evening compared to the morning, the mechanisms responsible for such variation are poorly understood.…”
Section: Effect Of Time-of-day Before Ramadanmentioning
confidence: 49%
“…In swimming, maximal muscle strength at a given velocity [i.e., power] and stroke parameters [i.e., swim speed (V), stroke rate (SR) and stroke length (SL)] are factors of great importance for performance. Also, morning-evening differences increase with the complexity of motor tasks; this effect has been reported not only with regard to overall performance but also with regard to its different components, such as maximal power and technical ability (Ferchichi et al, 2015(Ferchichi et al, , 2016 In view of the above considerations, the aim of the study is to examine the effect of Ramadan fasting on the diurnal variations of maximal cycle power and stroke parameters and consequently on swimming performance. We are not aware of any experimental evidence regarding effects of Ramadan fasting on the diurnal variations in stroke parameters in front crawl swimmers and overall swimming performance, and so the present study attempts to provide insights in this area.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the body temperature was higher in the evening hours. Ferchichi et al, (2015) found that the oral temperature was higher in the evening (17.00-19.00) than in the morning (07.00-09.00am).…”
Section: Body Temperaturementioning
confidence: 93%
“…It was also found that lung function was better in the evening. Ferchichi et al (2015) emitted that maximal swimming performances of swimmers were better in the evening than in the morning. Swimming speed, stroke rate, stroke length and motor organization parameters were found better in the evening hours.…”
Section: Aerobic Capacitymentioning
confidence: 98%